Cities and the rise of working women - Thor Berger; Mounir Karadja; Erik Prawitz (Research Institute of Industrial Economics (IFN), 2025)
We document that large cities were instrumental in shaping women's work and family outcomes in the early 20th century. We focus on migrants to Stockholm, Sweden's largest city, using representative, linked census data. Female migrants to Stockholm saw persistent changes in work and family outcomes over the life-cycle. Migrants were approximately 50 percentage points more likely to enter the labor force and less likely to marry or have children than their sisters migrating to rural areas. They experienced skill-upgrading and higher real incomes, without adverse mortality effects. Early structural shifts towards services partly explain these patterns.
Keywords: N93; I15; Q25; 330; Female labor force participation; Migration; Urbanization; Economic history